Deuterium Effect on Proliferation and Clonogenic Potential of Human Dermal Fibroblasts In Vitro - Zlatska, Olena V.; Zubov, Dmytro O.; Vasyliev, Roman G.; Syroeshkin, Anton V.; Zlatskiy, Ihor A. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(1): 049–053